2018
DOI: 10.1021/acs.analchem.7b05436
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Binding Components in Complex Sample Matrices on Recovery in Direct Immersion Solid-Phase Microextraction: Friends or Foe?

Abstract: The development of matrix compatible coatings for solid-phase microextraction (SPME) has enabled direct extraction of analytes from complex sample matrices. The direct immersion (DI) mode of SPME when utilized in conjunction with such extraction phases facilitates extraction of a wide range of analytes from complex matrices without the incurrence of fouling or coating saturation. In this work, mathematical models and computational simulations were employed to investigate the effect of binding components presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…A theoretical approach based on Langmuir's theory for the extraction kinetics of solid coating SPME has been previously addressed in the literature. 28,34 In brief, the amount of extract on the solid coating at equilibrium cs eq (mol•m −2 ) is given by…”
Section: ■ Theoretical Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A theoretical approach based on Langmuir's theory for the extraction kinetics of solid coating SPME has been previously addressed in the literature. 28,34 In brief, the amount of extract on the solid coating at equilibrium cs eq (mol•m −2 ) is given by…”
Section: ■ Theoretical Considerationsmentioning
confidence: 99%
“…26 In addition to the use of experimental techniques, mathematical modelling has been demonstrated as an excellent tool to determine the kinetics of SPME extraction in the presence of a binding matrix, as it allows for better predictions of results while minimizing the number of experiments that must be carried out during method development and routine analysis. 17,27,28 Alam et al first demonstrated the effects of a binding matrix on the extraction kinetics of SPME liquid coatings via development of a 2D model in COMSOL Multiphysics. 17 Gorecki et al and Zhou et al, in turn, demonstrated the extraction kinetics of solid coatings with the use of Langmuir's isotherms, which assumes isotropy of the fiber surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These molecules, having a moderate to high affinity constant towards the extraction phase, usually take several hours to reach equilibrium. 32 Therefore, in this section, the profiling of phosphopeptides from beta casein is used as a proof of concept. Beta casein is phosphorylated at five different serine residues: S-15, S-17, S-18, S-19, and S-36.…”
Section: Figurementioning
confidence: 99%
“…It is based on the sorption of analytes directly from the sample in one-step extraction and preconcentration of analytes [18,20]. The SPME has demonstrated its simplicity, usefulness, selectivity, and efficiency in the analysis of a broad range of compounds in several matrixes without requiring sample pretreatment [21].…”
Section: Introductionmentioning
confidence: 99%